The Composition of Placental Microbiota and Its Association With Adverse Pregnancy Outcomes - La, Xuena; Wang, Yuezhu; Xiong, Xu; Shen, Liandi; Chen, Weiyi; Zhang, Lifeng; Yang, Fengyun; Cai, Xushan; Zheng, Huajun; Jiang, Hong (Frontiers in Microbiology, 2022)
To verify whether the placenta harbors bacteria, and to explore the composition of placental microbiota (if yes) and its association with adverse pregnancy outcomes. The placental microbiota was detected by 16S rRNA gene sequencing technology. In the process of detecting placental samples, exogenous marine bacterial DNA that does not exist in the human body was artificially added to obtain a visible 16S band. At the same time, the sterile samples including scissors, sheet and cotton swabs in delivery and operating rooms were collected as the environmental control samples. As the results, a total of 2,621,009 sequences were obtained from 71 samples, 88.8% of which came from artificially added exogenous bacterial DNA, suggesting that the placenta contained low amounts of bacteria. After removing the OTUs (operational taxonomic units) that coexisted in the environmental controls, the placenta was annotated with 11 phyla, 22 classes, 43 orders, 79 families, and 157 genera. The β diversity analysis showed that there were significant differences in the placental microbiota between 10 women with gestational diabetes mellitus (GDM) (PAMOVA=0.01) or 19 women with premature rupture of membranes (PROM) (PAMOVA=0.004) and 21 women without adverse pregnancy outcomes, respectively. There were higher abundances of genera Bifidobacterium, Duncaniella, and Ruminococcus in the placenta samples of women with GDM. The genera of Bacteroides, Paraprevotella, and Ruminococcus were more enriched in the placental samples of women with PROM. The authors concluded that the placenta may harbor small amounts of microbiota, and significant differences in the dominant microbiota of placenta were observed between those pregnant women with and without adverse pregnancy outcomes.